Grey wolf optimizer for solving economic dispatch problem with valve-loading effects - Mohd Herwan, Sulaiman; Ing, Wong Lo; Zuriani, Mustaffa; Mohd Rusllim, Mohamed (Asian Research Publishing Network (ARPN), 2015)
This paper presents the application of recent swarm intelligence (SI) techniques in solving the Economic Dispatch (ED) problem. ED is known as one of the fundamental problems in power system operation which aimed to obtain the combination of the fuel based power generation so that the minimum cost can be achieved. In this paper, the effect of valve-loading will be considered in order to solve the complex optimization problem. The recent SI algorithm namely Grey Wolf Optimizer (GWO) will be utilized in this paper. To show the effectiveness of GWO in solving ED problem, 13-units and TAIPOWER 40-units systems are used and then the performance of GWO will be compared to the other recent techniques.